Creep-recovery behaviour of crumb rubber modified bitumen (CRMB) containing trans-polyoctenamer - Katman, Herda Yati; Ibrahim, Mohd Rasdan; Norhisham, Shuhairy; Ismail, Norlela; Rahman, Noorhazlinda Abd (International Research Publication House, 2018)
The main objective of this study is to analyse the creep-recovery behaviour of crumb rubber modified bitumen (CRMB) and crumb rubber modified bitumen containing Trans-polyoctenamer (CRMB-TOR). Moreover, the effect of different stress levels to creep parameters, namely, non-recoverable compliance (Jnr) and per cent recoveries (% R) are also studied. The Multiple Stress Creep Recovery (MSCR) test performed by Dynamic Shear Rheometer (DSR) was executed at 1 s creep loading with 9 s recovery over the multiple stress levels ranged from 25 to 25,600 Pa. In this study, CRMB was prepared with different percentages of crumb rubber namely 4%, 8% and 12%. The CRMB-TOR was prepared by adding 4.5% of TOR (by weight of crumb rubber) to each CRMB blend. Adding crumb rubber in the bitumen shows desirable change in creep-recovery behaviour. Moreover, application of TOR to the CRMB seems to further improve the creep parameters. An increase in creep-recovery parameters (low Jnr and high % R) can significantly improve the properties of bituminous mixtures. Thus, pavement constructed with good creep-recovery parameters would increase the service life with better rutting resistance.